After the Cold War: Does international trade and financial law matter? - Breskovski, Vassil (European University Institute, 1998)
Keywords: Cold War; Commercial law; Foreign economic relations; International Trade; International business enterprises; International economic relations; Post-communism; Russia (Federation)

States and markets : regulatory competition and the public law of banks - Padrós Reig, Carlos (European University Institute, 1997)
One of the most immediate questions that could be raised is that of the topic. Why banks?. Banks are a part of the economy which is especially prone to regulatory competition. Increasing financial globalization makes it difficult to maintain regulatory barriers and those remaining create costs that are avoided by regulatory arbitrage. Banks’ raw material is capital which is a highly mobile element. On the top of that, the longstanding experience of the US in the field, should be of some usefulness. Finally, banks are attractive since the European Union, by means of the Second Banking Directive, has undertaken a decisive step towards liberalisation. Regulatory competition in this field will be able to give us some clues into the direction of services regulation in general, and into the new institutional dimension of the Union. However, banks are only one type of financial actors. Securities and insurance industry are gradually occupying spaces traditionally reserved to banks - namely deposit collection and lending - and conversely, banks are extending their product range to cover securities and insurance activities, and are experiencing a process of disintermediation. Hence, it is increasingly impossible to distinguish among financial actors. Concentrating in one of them is just a research need in order to keep the study under manageable dimension. Still, banks remain a legally different industry because of their position in the economic gear and in the payment system. What could actually be questioned is the future of banks themselves or at least their different legal treatment In any case, the topic of financial services regulation is too large to be covered as a whole, so some subdivision is necessary. This has to be done acknowledging that divisions may not correspond to the reality of the marketplace.
Keywords: Banks; Competencia; Competition law; Law of Banks; Regulation

Two essays on political influence and the regulation of financial markets - Eckel, Doug (Virginia Tech, 1996)
I examine two potential instances of rent-seeking in financial markets in the 1980s. In the first essay I test whether managers engage in political activity designed to influence federal regulation of the market for corporate control. In the second, I examine whether firms in the financial services sector attempt to affect bank deregulation. Using Federal Election Commission data, I find campaign contributions by corporate political action committees (PACs) are negatively related to levels of inside ownership, my main proxy for managerial vulnerability to hostile tender offers. Contribution patterns for firms with less than 20% insider ownership are relatively highly correlated, and differ from those of firms with greater than 20% inside ownership. Low inside ownership firms have slightly higher levels of contributions to legislators on particular House and Senate committees proposing relevant legislation. However, when I analyze the impact of contributions on legislator support for regulation I find no statistical support for a theory of vote-buying. I conclude that corporate political behavior is tied to levels of inside ownership, and comprises an alternate index of manager-shareholder conflict. Using a similar approach to analyse the financial services industry, I also find significant patterns in political action committee (PAC) campaign contributions for depository (commercial bank and thrift) and non-depository (brokerage and insurance) sectors of the financial services industry during the 98th Congress (1983-84). Contributions by depository firm PACs appear not only to purchase access to legislators serving on important banking committees crucial to their interests, but are also a significant determinant of votes for repealing sections of the Glass-Steagall Act. Nondepository contributions do not appear to influence votes directly, even though the brokerage and insurance sectors effectively lobbied House Banking Committee chairman Fernand St Germain to enforce the regulatory status quo. When I measure the rents at stake in the legislation using a two-factor market model event study approach, I find that the passage of legislation in the Senate had a positive affect on depository firm returns, implying the sector's lobbying effort was justified. However non-depository PACs lobbied just as extensively, and did not experience significant abnormal returns over the same event period, even though this round of deregulation should have been a zero-sum game between the affected sectors of the industry. I then measure the correlation between the market value impacts of new legislation and contribution amounts for individual firms within the sectors. I find rents are correlated with political activity, even for firms in the non-depository sectors.
URI: http://hdl.handle.net/10919/39160
Keywords: Corporate control; Financial institutions; Financial markets; Regulation

The raising and maintenance of capital : a comparative study of some problems in the law of corporation finance - Ponnuswami, K. (McGill University, 1969)
This the sis is an in-depth comparative study and critical examination of several wide-ranging problems in the law of corporation finance of Britain and the principal jurisdictions of Canada and the United States of America. The problems examined include inadequate Capitalization, Stock-watering, Reduction of Capital, Purchase by a Corporation of its Shares, and Dividends. The the sis examines the trends and patterns in the different jurisdictions and appraises their merits and defects. The study concludes that the conceptual ambiguities and practical difficulties which abound in the laws of corporation finance are aggravated by the failure of the law to work out rational rules based on a clear and unifying policy for the raising and maintenance of capital. The necessity for such a policy is advocated in view of the inadequacy of the existing institutions and devices for the protection of the multifarious interests involved in corporate business enterprises. Cette thèse se présente sous la forme d'une étude comparative en profondeur et d'un examen critique de quelques problèmes du droit des corporations financières de Grande Bretagne et des principales juridictions du Canada et des Etats-Unis d'Amérique. Y sont étudiés entre autres l'insuffisance de capital, la dilution de capital, la réduction de capital, le rachat de ses actions par une corporation et les problèmes concernant les dividendes. On y examine ensuite les tendances et positions de ces différentes juridictions, pour en évaluer les mérites et les défauts. En conclusion cette étude montre que les ambiguités conceptuelles et les difficultés pratiques qui abondent dans le droit des corporations financières sont aggravées par l'insuffisance de la loi à élaborer de règles rationnelles, basées sur une politique claire et uniforme de souscription et de maintien du capital. La nécessité d'une telle politique semble évidente lorsque l'on considère l'imperfection des institutions actuelles et des moyens de protection des multiples intérêts impliqués dans les corporations commerciales.
https://escholarship.mcgill.ca/concern/theses/cv43nx97w
Keywords: Capitalization; Corporations; Finance; Reduction of capital; Shares